Impact of Subacute Exposure to T-2 Toxin and Zearalenone on the Pharmacokinetics of Midazolam as CYP3A Probe Drug in a Porcine Animal Model: A Pilot Study - Schelstraete, Wim; Devreese, Mathias; Croubels, Siska (Frontiers in Pharmacology, 2019)
Cytochrome P450 enzymes (CYP) are important catalyzing proteins involved in the biotransformation of endogenous and xenobiotic compounds. However, their expression and/or activity can be altered by exposure to contaminants such as mycotoxins. In vitro incubations in porcine hepatic microsomes revealed a potent inhibition of the midazolam (CYP3A) biotransformation by T-2 toxin (T-2) (Ki = 27.0±3.97 µM) and zearalenone (ZEA) (Ki = 1.1±0.22 µM). Consequently, the in vivo impact of two weeks exposure to T-2 (1,000 µg/kg feed) or ZEA (500 µg/kg feed) on the pharmacokinetics (PK) of midazolam as a CYP3A probe drug was investigated in pigs, and was compared to a control group receiving no mycotoxins. Midazolam was chosen as this drug undergoes substantial first-pass metabolism in humans with equal contribution of the intestine and liver. Each pig received a single intravenous (0.036 mg/kg BW) and oral (0.15 mg/kg BW) dose of midazolam. For the IV bolus no differences were observed in pharmacokinetics between control and mycotoxins exposed groups. However, oral plasma concentration-time profiles showed quantitative differences in absolute oral bioavailability F [p-value (ANOVA) = 0.022], AUC_0-inf (µg*h/L) [p-value (ANOVA) = 0.023], Ke (1/h) [p-value (ANOVA) = 0.004], and Ka (1/h) [p-value (ANOVA) = 0.031. Although only differences in Ke estimates after oral administration reached significance in the post-hoc analysis due to inequality of the variances. We hypothesize that the observed trends after ZEA and T-2 exposure are related to the cytotoxic effect of T-2, resulting in an increased absorption rate constant Ka. For ZEA, an inhibition of the CYP3A enzymes is suggested based on the in vitro inhibition potential and increase in oral bioavailability. Further research is required to confirm the current hypothesis.